The Campus Teaching Program Batch 4 At YP Utama Junior High School Medan Tembung - Sahlan Tampubolon; Kristi Dwi Inggrid Hutasoit (Departement of Mathematics Education, 2023)
Campus teaching is part of the learning and teaching activities in the basic education unit of the Independent Learning and Independent Campus program (MBKM) which aims to provide opportunities for students to learn for one semester in developing themselves through activities outside the campus. The teaching campus aims to equip students with a variety of skills and skills by being a partner of teachers and schools in the development of learning models, as well as fostering creativity and innovation in learning so that it has an impact on strengthening literacy and numeracy learning in schools. The teaching campus program opens space for students to be able to apply their skills and knowledge in helping students in basic education units. This Program provides an opportunity for students to actualize their interests, passion, and desires. In addition, students are expected to be an inspiration for students to expand their ideals and insights.